Features of the restaurant market and consumer behavior in the Moscow restaurant business segment: study results - A. N. Timokhovich (Вестник университета)
The article presents a comprehensive study results aimed at identifying peculiarities of the restaurant market and consumer behavior in the Moscow restaurant business segment. Within the framework of the research three stages have been realized. At the first stage the Moscow restaurant market macroenvironment has been analyzed to identify external factors of influence on modern restaurant business. The external factors of positive and negative impact on the restaurant industry development have been structured and described. At the second stage to identify the main trends of the Moscow restaurant market the method of content analysis of the Moscow restaurant business establishments sites with high rating indicators based on the Yandex neural network data was used. The main trends of the Moscow restaurant market are: restaurants’ focus on preparing healthy food and vegetarian cuisine; use of farm products and local ingredients in prepared dishes; technological innovations implementation that simplify consumer experience; focus on the principles of sustainable development and environmental friendliness in the business model; restaurant formats variety. At the third stage of the study, a survey has been conducted among visitors to Moscow restaurants and cafes to identify consumer behavior. The identified consumer practices in the restaurant market indicate, on the one hand, active involvement of the audience in visiting Moscow restaurants, cafes, and bars, and on the other hand, the use of restaurant meal delivery services via restaurant websites or mobile applications. The dominant influence of rational factors in consumers’ choice of a restaurant to visit and changes in the consumer motivation structure when visiting restaurants and cafes have been revealed.